PERANAN MANAJEMEN PAJAK PENGHASILAN DALAM MEMINIMALKAN BEBAN PAJAK PENGHASILAN TERUTANG CV PCIW - Christine Sada Meyranda Marpaung (Jurnal Pitis AKP, 2017)
Income tax is an expense that must be paid by the taxpayer to the State because of theincome that the taxpayer earns. For taxpayers, the amount of tax expense is as little aspossible. By utilizing the tax collection system which is a self assessment system,taxpayers can calculate their own income tax amount that must be paid to the State sothat the taxpayer's business arises to minimize the tax expense on income owed. Thepurpose of this research is to find out the taxpayer's efforts in minimizing the incometax payable which can be done by applying income tax management in accordance withits functions namely tax planning, tax organizing, tax leading and tax controlling. Inthis research, tax planning is carried out by the author by analyzing whether there arecosts that were previously not deductible to be deductible, analyzing whether there isincome that was taxable can be changed to non taxable. Tax organizing, tax leadingand tax controlling are tax management functions that support the effectiveness of theimplementation of income tax management in minimizing the income tax expense.